Expanded gene and taxon sampling of diplomonads shows multiple switches to parasitic and free-living lifestyle - Wiśniewska, Monika M; Salomaki, Eric D; Silberman, Jeffrey D; Terpis, Kristina X; Mazancová, Eva; Táborský, Petr; Jinatham, Vasana; Gentekaki, Eleni; Čepička, Ivan; Kolisko, Martin (BMC biology, 2024)
BACKGROUND: Diplomonads are anaerobic flagellates classified within Metamonada. They contain both host-associated commensals and parasites that reside in the intestinal tracts of animals, including humans (e.g., Giardia intestinalis), as well as free-living representatives that inhabit freshwater and marine anoxic sediments (e.g., Hexamita inflata). The evolutionary trajectories within this group are particularly unusual as the free-living taxa appear to be nested within a clade of host-associated species, suggesting a reversal from host-dependence to a secondarily free-living lifestyle. This is thought to be an exceedingly rare event as parasites often lose genes for metabolic pathways that are essential to a free-living life strategy, as they become increasingly reliant on their host for nutrients and metabolites. To revert to a free-living lifestyle would require the reconstruction of numerous metabolic pathways. All previous studies of diplomonad evolution suffered from either low taxon sampling, low gene sampling, or both, especially among free-living diplomonads, which has weakened the phylogenetic resolution and hindered evolutionary insights into this fascinating transition. RESULTS: We sequenced transcriptomes from 1 host-associated and 13 free-living diplomonad isolates; expanding the genome scale data sampling for diplomonads by roughly threefold. Phylogenomic analyses clearly show that free-living diplomonads form several branches nested within endobiotic species. Moreover, the phylogenetic distribution of genes related to an endobiotic lifestyle suggest their acquisition at the root of diplomonads, while traces of these genes have been identified in free-living diplomonads as well. Based on these results, we propose an evolutionary scenario of ancestral and derived lifestyle transitions across diplomonads. CONCLUSIONS: Free-living taxa form several clades nested within endobiotic taxa in our phylogenomic analyses, implying multiple transitions between free-living and endobiotic lifestyles. The evolutionary history of numerous virulence factors corroborates the inference of an endobiotic ancestry of diplomonads, suggesting that there have been several reversals to a free-living lifestyle. Regaining host independence may have been facilitated by a subset of laterally transferred genes. We conclude that the extant diversity of diplomonads has evolved from a non-specialized endobiont, with some taxa becoming highly specialized parasites, others becoming free-living, and some becoming capable of both free-living and endobiotic lifestyles.
Keywords: Transcriptomics; Phylogeny; Phylogenetics; biologická evoluce; Biological Evolution; fylogeneze; Diplomonads; Phylogenomics; Diplomonadida; Parasitic ancestry signals